Innovation of Project Assessment Instruments for Maharatul Qiro'ah in Grade IX Arabic Textbooks - Muhammad Hamdani; Yusron Hidayat; Muhammad Aenurrafiq; Mahsur; Kamariah (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
This study aims to develop innovative project assessment instruments that are relevant to improving reading skills in Arabic language learning. The focus of this study is on the Grade IX Arabic Textbook published by the Ministry of Religious Affairs of the Republic of Indonesia. The background of this research is based on the need for assessment methods that can encourage students to understand texts deeply, critically, and contextually, in accordance with the demands of today's learning. This study used library research method strengthened by content analysis to explore the optimal strategies and approaches in developing project-based assessment instruments. The findings show that the instrument can be designed through activities such as text analysis, summarization, and interpretive discussion. The instrument is accompanied by an evaluation rubric that covers vocabulary understanding, text structure, content analysis, and the ability to reflect the meaning of the text in the context of daily life. This innovation is expected to improve students' reading ability while honing critical thinking skills and appreciation of Arabic texts. In addition, this instrument provides teachers with a comprehensive and measurable evaluation tool to objectively monitor student progress. This research makes a significant contribution to the development of Arabic language learning in Indonesia through an interactive and applicable approach, so that it can meet the needs of modern education in improving maharatul qiro'ah effectively and continuously.